Long-term effects of new progressive group balance training for elderly people with increased risk of falling – a randomized controlled trial. (May 2013) - Halvarsson, Alexandra; Franzén, Erika; Farén, Elin; Olsson, Elisabeth; Oddsson, Lars; Ståhle, Agneta
Objective: To evaluate the long-term effects of a progressive and specific balance group-based program in healthy elderly individuals with increased risk of falling. Design: Follow-up of a randomized controlled trial at nine and 15 months on a population that has previously been described at three months. Setting: The study was conducted in Stockholm, Sweden. Subjects: 59 community-dwelling elderly (age 67–93 years), recruited by advertisement, were randomly allocated to training or to serve as controls. Intervention: Group balance training three times per week during 12 weeks with a 15 month follow-up time. Main measures: Participants were assessed at baseline, three, nine, and 15 months thereafter for gait function (preferred and fast walking), rapid step execution (single and dual task), fear of falling, and likelihood of depression. Results: Fast gait speed ( p = 0.004), dual task step execution ( p = 0.006) and fear of falling ( p = 0.001) were still improved in the training group at nine months follow-up. Only self-perceived fear of falling remained significantly improved ( p = 0.012) at 15 months follow-up. Although fast gait speed had decreased to baseline level in the training group (1.49 m/s) it remained significantly higher than in the control group (1.37 m/s) at the end of the study, a difference between the groups that was not seen at baseline. Conclusion: This training program provided important positive short and long-term benefits to gait, balance function, and fear of falling.